Perencanaan dan Perancangan Lanskap Taman Maju Bersama Haji Saibun di Kelurahan Jati Padang, Jakarta Selatan - Moh. Sanjiva Refi Hasibuan; Ray March Syahadat; Lasmaria Sidabutar (Jurnal Infrastruktur, 2020)
Taman Maju Bersama (TMB) is a program of DKI Jakarta Provincial Government in providing Green Open Space (RTH) using community based planning approach (bottom-up). The planning and design process of TMB Haji Saibun in South Jakarta goes through several stages starting from field survey activities, Focus Group Discussion (FGD), site analysis, programming and concept, and design process. FGD carried out in three stages, firstly in the early stages of planning to accommodate the community aspirations and needs for the park, secondly in order to get input from the community on the result of the design that has been made, and thirdly to socialize the final design of the park to be implemented later. The design of TMB Haji Saibun applies the general concept of Betawi Park to raise the local character of the region, and the specific concept of park design for various age levels. Park spaces area divided into 4 (four) main spaces that will accommodate the needs of community from children, adults, parents or the elderly.